Vacuum‐Healing of Grain Boundaries in Sodium‐Doped CuInSe2 Solar Cell Absorbers - Babbe, Finn; Nicoara, Nicoleta; Guthrey, Harvey; Valle, Nathalie; Ramirez Sanchez, Omar; Aureau, Damien; Elanzeery, Hossam; Sharma, Deepanjan; Virtuoso, José Luís; Audinot, Jean‐Nicolas; Zelenina, Anastasiya; Gharabeiki, Sevan; et al. (Advanced energy materials, 2023)
Alkali metal doping and grain boundaries (GB) have been at the center of attention within the Cu(In,Ga)(S,Se)2 photovoltaics community for years. This study provides the first experimental evidence that the GB of sodium‐doped CuInSe2 thin films may undertake reversible oxidation even at room temperature, whereas undoped films may not. The findings are corroborated by cathodoluminescence imaging, secondary ion mass spectrometry, and Kelvin probe force microscopy on air‐exposed films subsequently subject to vacuum. A thermochemical assessment identifies the likely solid–gas equilibria involved. These reactions open new research questions with respect to the beneficial role played by alkali metal dopants in chalcopyrite solar cells and may steer the community toward new breakthroughs. The surface and grain boundaries of sodium‐doped CuInSe2 thin film solar cell absorbers undertake reversible oxidation, unlike undoped films. The topographical features of the films observed by electron, He‐ion, and Kelvin probe force microscopies are cross‐correlated by cathodoluminescence spectroscopy, secondary ion mass spectrometry, and contact potential difference imaging, before and after a long time under vacuum.